Do Parent–Adolescent Discrepancies in Family Functioning Increase the Risk of Hispanic Adolescent HIV Risk Behaviors? - CORDOVA, DAVID (2014)
In the family-based prevention science literature, family functioning, defined as positive parenting, parental involvement, family cohesion, family communication, parental monitoring of peers, and parent–adolescent communication, has been shown to ameliorate HIV risk behaviors in Hispanic youth. However, the majority of studies have relied solely on parent or adolescent reports and we know very little about parent–adolescent family functioning discrepancies. Therefore, the purpose of this study was to examine whether and to what extent parent–adolescent discrepancies in family functioning increased the risk of HIV risk behaviors, including substance use and sexual risk behaviors, and whether these associations vary as a function of acculturation and youth gender. A total of 746 Hispanic 8th grade youth and their primary caregivers were included in the study. Structural equation modeling findings indicate that parent–adolescent family functioning discrepancies are associated with an increased risk of Hispanic adolescent HIV risk behaviors, including lifetime and past 90-day alcohol and illicit drug use, and early sex initiation. In addition, study findings indicate that results vary by acculturation and youth gender. Findings are discussed in the context of existing family-based research and practice in preventing and reducing HIV risk behaviors among Hispanic youth and their families.